REGRAS: an auxiliary program for pattern recognition and substructure elucidation of monoterpenes. Issue 2 (2001) - Ferreira Ferreira, Marcelo J. P. Marcelo J. P.; Rodrigues Rodrigues, Gilberto V. Gilberto V.; Brant Brant, AntÔnio J. C. AntÔnio J. C.; Emerenciano Emerenciano, Vicente P. Vicente P.
Abstract : The main purpose of this paper is to present a procedure that utilizes 13 C NMR for pattern recognition and substructure elucidation of monoterpenes. By this reason, a novel version of the REGRAS program was developed for the specialist SISTEMAT system. This program carries out an analysis of the 13 C NMR data from a given compound and, from characteristic chemical shift ranges, recognizes the substructures and the skeleton present in a compound. At the end of this procedure, the program displays as analysis results the likely skeletons and substructures of the substance in question. The REGRAS program was tested on skeleton elucidation of 30 monoterpenes from the most varied skeleton types, exhibiting excellent results in skeleton and substructure prediction processes.